2022
DOI: 10.26603/001c.32591
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Task Gait Performance Following Head Impact Exposure in Male and Female Collegiate Rugby Players

Abstract: Background Gait impairments have been well-studied in concussed athletes. However, the sex-specific effect of cumulative head impacts on gait is not well understood. When a cognitive task is added to a walking task, dual-task gait assessments can help amplify deficits in gait and are representative of tasks in everyday life. Dual-task cost is the difference in performance from walking (single-task) to walking with a cognitive load (dual-task). Purpose The objectives of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…13,14,16,18 The current study also found that the increased DTC was not experienced for the same spatiotemporal parameters of gait or to the same degree by males and females with acute SRC, suggesting that different compensatory patterns to perform dual-task gait may be evident based on sex in similar samples. Recently, Kieffer et al 30 found that even in collegiate athletes, who are presumed to function with more developed neuromuscular abilities, DTCs for several parameters of gait varied irrespective of sex but were overall higher for females. When assessing adolescent athletes within 14 days of concussion, Howell et al 16 found that females typically experienced a significantly greater DTC for cadence (not measured in the current study), whereas a separate study reported inconsistent variability in several cognitive, neuromotor, and oculomotor functions according to sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14,16,18 The current study also found that the increased DTC was not experienced for the same spatiotemporal parameters of gait or to the same degree by males and females with acute SRC, suggesting that different compensatory patterns to perform dual-task gait may be evident based on sex in similar samples. Recently, Kieffer et al 30 found that even in collegiate athletes, who are presumed to function with more developed neuromuscular abilities, DTCs for several parameters of gait varied irrespective of sex but were overall higher for females. When assessing adolescent athletes within 14 days of concussion, Howell et al 16 found that females typically experienced a significantly greater DTC for cadence (not measured in the current study), whereas a separate study reported inconsistent variability in several cognitive, neuromotor, and oculomotor functions according to sex.…”
Section: Discussionmentioning
confidence: 99%
“…When assessing adolescent athletes within 14 days of concussion, Howell et al 16 found that females typically experienced a significantly greater DTC for cadence (not measured in the current study), whereas a separate study reported inconsistent variability in several cognitive, neuromotor, and oculomotor functions according to sex. 30 With respect to varying gait strategies, Table 4 provides valuable data for individual assessments by each participant during initial testing who experienced a DTC greater than one SD compared to healthy references in at least one parameter of gait. Male participant A and female participant B, both with acute SRC, experienced the DTC on at least three parameters, representing athletes with the most negative side effects Spatiotemporal Parameters of Gait Among Adolescent Athletes with Concussion When Performing a Visuospatial Cognitive Task Asterisk (*) denotes the percentage of the male and female acute (20% and 83%, respectively) and chronic (10%, and 29%, respectively) cases that experienced a DTC greater than one SD compared to healthy athlete reference values for at least one spatiotemporal parameter of gait.…”
Section: Discussionmentioning
confidence: 99%
“…rugby). 39 Therefore, other sensor systems, such as headband-mounted sensors and skin patch sensors, have utility in providing estimates of head impact exposure for athletes who do not typically wear mouthguards, such as soccer players. In a field study using the SIM-G sensor, Patton et al 13 identified that less than 10% of sensor events recorded in high school soccer games were false positives suggesting the SIM-G can provide an accurate estimate of head impact exposure on field.…”
Section: Discussionmentioning
confidence: 99%
“…A recording threshold of 5 g linear acceleration at the head center of gravity was selected, given that the previous threshold of 10g lacked sensitivity in capturing mild headers [1,32]. Previous studies have established the validity of the Prevent Biometric custom-fit iMG [25,33]. Liu et al [33] found the Prevent Biometric custom-fit iMG to perform best in laboratory dummy headform test-ing with lower mean relative errors of 4.9%, 4.6%, and 2.5% for peak angular acceleration, angular velocity, and linear acceleration, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Patch devices with these sensors may provide erroneous measurements due to poor skull coupling (soft tissue artifacts), which can result in overestimations of HAE magnitude [24]. Alternatively, instrumented mouthguards (iMGs) have been shown to be more accurate by directly coupling to the upper dentition and thus skull, reducing soft tissue artifacts and making them the preferred choice for measuring HAEs in real-time [24,25]. From this, researchers have identified the penalty box to be a high-risk area for concussive injury, with ball speeds frequently exceeding 120 km/h [26] and peak acceleration exposures to the head 150% greater than those noted in hockey or American football [27].…”
Section: Introductionmentioning
confidence: 99%